Effect of dexmedetomidine on Nociception Level Index-guided remifentanil antinociception: A randomised controlled trial. Issue 5 (May 2021) - Coeckelenbergh, Sean; Doria, Stefano; Patricio, Daniel; Perrin, Laurent; Engelman, Edgard; Rodriguez, Alexandra; Di Marco, Livia; Van Obbergh, Luc; Estebe, Jean-Pierre; Barvais, Luc; Kapessidou, Panayota
Abstract : BACKGROUND: The effect of dexmedetomidine on Nociception Level Index-guided (Medasense, Israel) antinociception to reduce intra-operative opioid requirements has not been previously investigated. OBJECTIVE: We aimed to determine if low-dose dexmedetomidine would reduce remifentanil requirements during Nociception Level Index-guided antinociception without increasing complications associated with dexmedetomidine. DESIGN: Double-blind randomised controlled trial. SETTING: Two university teaching hospitals in Brussels, Belgium. PATIENTS: American Society of Anesthesiologists 1 and 2 patients ( n  = 58) undergoing maxillofacial or cervicofacial surgery under propofol--remifentanil target-controlled infusion anaesthesia. INTERVENTIONS: A 30 min infusion of dexmedetomidine, or equal volume of 0.9% NaCl, was infused at 1.2 μg kg −1  h −1 immediately preceding induction and then decreased to 0.6 μg kg −1  h −1 until 30 min before ending surgery. Nociception Level Index and frontal electroencephalogram guided the remifentanil and propofol infusions, respectively. MAIN OUTCOMES: The primary outcome was the remifentanil requirement. Other outcomes included the propofol requirement, cardiovascular status and postoperative outcome. RESULTS: Mean ± SD remifentanil (3.96 ± 1.95 vs. 4.42 ± 2.04 ng ml −1 ; P  = 0.0024) and propofol (2.78 ± 1.36 vs. 3.06 ± 1.29 μg ml −1 ; P  = 0.0046) TCI effect site concentrations were lower in the dexmedetomidine group at 30 min postincision and remained lower throughout surgery. When remifentanil (0.133 ± 0.085 vs. 0.198 ± 0.086 μg kg −1  min −1 ; P  = 0.0074) and propofol (5.7 ± 2.72 vs. 7.4 ± 2.80 mg kg −1  h −1 ; P  = 0.0228) requirements are represented as infusion rates, this effect became statistically significant at 2 h postincision. CONCLUSION: In ASA 1 and 2 patients receiving Nociception Level Index-guided antinociception, dexmedetomidine decreases intra-operative remifentanil requirements. Combined frontal electroencephalogram and Nociception Level Index monitoring can measure dexmedetomidine's hypnotic and opioid-sparing effects during remifentanil-propofol target-controlled infusion anaesthesia. TRIAL REGISTRATIONS: Clinicaltrials.gov: NCT03912740, EudraCT: 2018-004512-22. Abstract : Supplemental Digital Content is available in the text